SISTEM PENDUKUNG KEPUTUSAN PENENTUAN DEPARTEMEN TERBAIK DALAM PROGRAM 5R MENGGUNAKAN METODE AHP - Wiyanto W (Jurnal Pelita Teknologi, 2019)
The implementation of a quality management system is inseparable from the work culture of the company concerned. The better the work culture of the organization, the more effective the ISO 9001 quality management system is implemented. As with the health and safety management system or commonly called OHSAS 18001 K3 management, and the ISO 14001 environmental management system it cannot be separated from the application of work culture 5R. If the implementation of the 5R culture goes well, the quality management system, K3 system and environmental management system will certainly have a good effect on its implementation. PT. Kayu Permata has a 5R program which is held regularly every Friday of the week. In the process of determining the best department, it can also be done using a decision support system by calculating the Analytical Hierarchy Process (AHP) method so that selection can be done quickly, precisely and accurately. Keywords: 5R Program,K3 System, AHP Method, ISO.